1990
DOI: 10.1063/1.102543
|View full text |Cite
|
Sign up to set email alerts
|

Short time electron cyclotron resonance hydrogenation of polycrystalline silicon thin-film transistor structures

Abstract: Electron cyclotron resonance plasmas have been used to produce the most effective, shortest time plasma hydrogenation of thin-film polycrystalline silicon transistors yet reported. We demonstrate that significant improvement in device characteristics can be achieved with these plasmas using exposure times of the order of only 1 min and that 5 min exposures give saturated characteristics of a 2 V threshold voltage, a 65 cm2/V s mobility, and a 107 on/off ratio. We also explore the pressure and power level depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…In surface engineering H 2 -containing plasmas have a wide range of applications, for example in etching 1 , film deposition 2-7 and surface passivation, hydrogenation and oxide reduction [8][9][10][11] . Furthermore, H 2 -Ar mixtures were successfully applied for hydrogenation of thin film transistors 12 and to control the surface properties of polymers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In surface engineering H 2 -containing plasmas have a wide range of applications, for example in etching 1 , film deposition 2-7 and surface passivation, hydrogenation and oxide reduction [8][9][10][11] . Furthermore, H 2 -Ar mixtures were successfully applied for hydrogenation of thin film transistors 12 and to control the surface properties of polymers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…H 2 -containing plasmas have a wide range of technical applications in etching 1 , film deposition 2-7 and surface passivation, hydrogenation and oxide reduction [8][9][10][11] . H 2 -Ar mixtures were successfully applied for hydrogenation of thin film transistors 12 and to control the surface properties of polymers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most of the methods proposed in the literature for the preparation of silicon oxide have involved either processing temperatures above 400°C or the use of silane during deposition and a new method without these limitations is required to prepare high quality and reliable devices at a low temperature. Now, it has been shown that RF plasma hydrogenation of evaporated amorphous Si films can lead to the formation of nano-crystalline layers suitable for thin film transistor fabrication and optical applications [4,5]. In addition, the use of plasma hydrogenation for the formation of nano-porous silicon from nano-crystalline silicon at maximum processing temperatures below 400°C has been recently reported [6,7].…”
Section: Introductionmentioning
confidence: 98%